Non-ideal effects on the typical trailing edge shock pattern of ORC turbine blades. (September 2017) - Vimercati, D.; Gori, G.; Spinelli, A.; Guardone, A.
Abstract: At the trailing edge of supersonic high-pressure turbine vanes, a typical shock pattern, the so-called fish-tail shocks, originates due to the flow rotation imposed by its finite thickness. In addition, shock and shock/fan systems can arise in case of a post-expanded channel design or at off-design conditions. ORC turbine stator blades are particularly prone to this phenomena since they are designed to provide a high outlet Mach number, especially at the first stage. In the close proximity of the saturation curve, near the critical point, molecularly complex organic fluids for ORC applications may exhibit a number of non-ideal gasdynamic effects, including a remarkable dependency of the shock properties on the upstream thermodynamic state of the fluid, at a fixed upstream Mach number. The influence of thermodynamic conditions on the shock pattern is assessed as a function of the flow deviation and compared against the ideal gas case, for which the shock properties depends on the upstream Mach number only. Non-ideal effects are investigated here using siloxane vapor MDM (Octamethyltrisiloxane, C8 H24 O2 Si3 ), as an exemplary organic fluid. The present results can be arguably extended to most vapors currently employed in ORC applications.